Multilevel Marketing Strategy in PT. Oriflame Medan as a Basic Steps for Students of Business Studies - Pasaribu, I M (KnE Social Sciences, 2018)
The marketing strategy is designed to determine the direction, marketing objectives in the business related to market segmentation and marketing mix elements. This study aims to determine the marketing strategy that includes market segmentation, product, price, distribution and promotion strategy. Network marketing (MultiLevel Marketing/MLM) is now getting a lot of interest by the people of Indonesia, especially in the city of Medan. From the results of the existing reality, researchers try to see marketing strategies undertaken by Multi-Level Marketing (MLM) at PT. Oriflame Indonesia in Medan city, where the purpose of this research is to know the marketing strategy applied by Multi-Level Marketing (MLM) at PT. Oriflame Indonesia in Medan city. The purpose of this research is to determine whether multi-level marketing strategy (MLM) affects the business beginners viewed from the number of members at multi-level marketing (MLM) PT. Oriflame field that holds the status as a student. Multi-Level Marketing (MLM) is a way or method of selling goods directly to consumers through a network developed by distributor members. Multi-Level Marketing that has products/goods to sell to consumers. The research method used is descriptive qualitative method approach that means the research produces descriptive data as data derived from the words result of interview with observed behavior. The observed behavior is none other than that of the members of Multi-Level Marketing PT. Oriflame Medan that acted as a population at the same time becoming a sample member of the company Multi-Level Marketing still bearing the status of Medan Students. The results show that if viewed from the marketing strategy of multi-level marketing (MLM), apply a structured marketing strategy with positive and significant influence of the landing that always given from the upline to its downline as a new member, the application discusses the overall strategy implemented in market products of PT. Oriflame so that the implementation has a significant influence on the beginner business who was cultivated member in Medan who status is of a student. This means the hypothesis is accepted. Keywords: Multilevel Marketing Strategy, basic steps for business